2017
DOI: 10.1080/17538157.2017.1297305
|View full text |Cite
|
Sign up to set email alerts
|

Toward a patient-centered ambulatory after-visit summary: Identifying primary care patients’ information needs

Abstract: The results of this study can be used to inform the development of an after-visit summary that assists patients to fully understand their treatment plan, which may improve treatment adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Our approach to thematic analysis included a deductive, realist approach to the data using a theoretical frame to identify key themes across the dataset in response to predefined research questions. Both RJK and SMC are experienced with qualitative research, with RJK a family physician researcher and SMC a long-time project director with a public health, diversity, and patient needs perspective [48][49][50][51][52][53]. First, researchers RJK and SMC became familiar with the data by reviewing and checking accuracy of verbatim transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach to thematic analysis included a deductive, realist approach to the data using a theoretical frame to identify key themes across the dataset in response to predefined research questions. Both RJK and SMC are experienced with qualitative research, with RJK a family physician researcher and SMC a long-time project director with a public health, diversity, and patient needs perspective [48][49][50][51][52][53]. First, researchers RJK and SMC became familiar with the data by reviewing and checking accuracy of verbatim transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who accessed their clinical information online through their EHR strongly believed that they would be able to access their clinical information quickly and efficiently, track visits and tests, and reinforce their understanding of physicians' instructions. 8,9,11,12,[14][15][16]19,25 Similarly, a randomized study by Pavlik et al 15 found that satisfaction with the clinical visit summary was significantly associated with online access through the electronic medical record.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that patient needs vary based on health contexts of chronic illness vs acute medical situations, and longitudinal primary care vs specialty care. 26,27 Current solutions provided by EHR vendors may not meet the needs of patients, caregivers, or providers. 26 Health care providers have the opportunity to push the development of health care visit summaries tailored to patient learning styles, incorporating technological solutions such as audio and video to supplement printed materials.…”
Section: Discussionmentioning
confidence: 99%